The Portuguese on the Swahili coast: buildings and language - Freeman-Grenville, Greville Stewart Parker (Studia: revista semestral, 1989)
Except for a few months in Mombasa in 1728-1729, the Portuguese occupation of East Africa, that is the coast of Kenya and Tanzania, together with the islands of Pemba and Zanzibar, effectively ceased in 1698. In this article, the author describes what has remained of the Portuguese in the area: the buildings, and the loanwords in the Swahili language, particularly the names of useful food crops and fruit trees. App. (words of Portuguese origin in Swahili), bibliogr.
Keywords: Relations -- Zanzibar -- Portugal

The Portuguese period in East Africa - Strandes, Justus (The East African Literature Bureau, 1968)
with topographical notes by J.S. Kirkman
Keywords: Relations -- Zanzibar -- Portugal